(untitled) (History Journal «Jerónimo Zurita», 2024)
Both the battle of Salado and the conquest of Algeciras were essential events in the conformation of the conquering image of Alfonso XI. The aim of this work is to reflect on the importance of royal propaganda in the shaping of the image of the past and in the construction of the historical event. To this end, I analyse the echo of this image in royal chronicles and in other discursive and communicative contexts, the common ideas under the texts, the conversion of both milestones into chronological references and their use as structural boundaries in historiographical texts.